2019
DOI: 10.1007/s00209-019-02372-z
|View full text |Cite
|
Sign up to set email alerts
|

Quaternionic loci in Siegel’s modular threefold

Abstract: Let Q D be the set of moduli points on Siegel's modular threefold whose corresponding principally polarized abelian surfaces have quaternionic multiplication by a maximal order O in an indefinite quaternion algebra of discriminant D over Q such that the Rosati involution coincides with a positive involution of the form α → µ −1 αµ on O for some µ ∈ O with µ 2 + D = 0. In this paper, we first give a formula for the number of irreducible components in Q D , strengthening an earlier result of Rotger. Then for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 37 publications
(141 reference statements)
0
11
0
Order By: Relevance
“…In this section we shall introduce and review some properties of Shimura curves on Siegel's modular threefold. The materials are taken from [10,12,13,14].…”
Section: Shimura Curves On Siegel's Modular Threefoldmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section we shall introduce and review some properties of Shimura curves on Siegel's modular threefold. The materials are taken from [10,12,13,14].…”
Section: Shimura Curves On Siegel's Modular Threefoldmentioning
confidence: 99%
“…In [10], in order to determine the exact number of Shimura curves in Q D,1 , Lin and Yang showed that there is a one-to-one correspondecne between Shimura curves in Q D,1 and GL(2, Z)-equivalence classes of positive definite binary quadratic forms of discriminant −16D such that all integers a represented by the quadratc form satisfy a ≡ 0, 1 mod 4 and…”
Section: Shimura Curves On Siegel's Modular Threefoldmentioning
confidence: 99%
See 3 more Smart Citations